1971
DOI: 10.1017/s0022112071000053
|View full text |Cite
|
Sign up to set email alerts
|

A study of free jet impingement. Part 1. Mean properties of free and impinging jets

Abstract: In this, the first part of a two-part experimental study of the behaviour of impinging jets, the mean properties of the flow field are established. Velocity profiles are given for three types of jet flow issuing from a circular convergent nozzle. Measured distributions of surface pressure are given which result when the jets impinge both normally and obliquely at various distances on several surface shapes. The pressure distributions are used to compute the radial velocity gradient at the impingement stagnatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
174
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 517 publications
(188 citation statements)
references
References 5 publications
13
174
1
Order By: Relevance
“…The parameters of these releases are given in Table 1. Figure 2 depicts predictions of the normalized centreline axial velocity, plotted against experimental data for a highly under-expanded air jet [5]. As expected, the unmodified k-İ model over-predicts the jet mixing, leading to an over-dissipative solution.…”
Section: Mathematical Modellingmentioning
confidence: 63%
“…The parameters of these releases are given in Table 1. Figure 2 depicts predictions of the normalized centreline axial velocity, plotted against experimental data for a highly under-expanded air jet [5]. As expected, the unmodified k-İ model over-predicts the jet mixing, leading to an over-dissipative solution.…”
Section: Mathematical Modellingmentioning
confidence: 63%
“…Figure 6 demonstrates the effect of these modifications upon the axial centre-line velocity profile predictions of a highly under-expanded air jet, reported by (Donaldson and Snedeker, 1971). The standard k-ε model is clearly too dissipative, leading to an early decay of the compression/decompression cycle.…”
Section: Turbulence Modellingmentioning
confidence: 97%
“…The three major flow categories of a gas flow jet issued from a circular nozzle are subsonic, moderately under-expanded jet, and highly under-expanded; see Figure 4 for under-expanded cases [31]. When the critical pressure ratio is reached, which is 1.889 for hydrogen, a very weak normal shock is expected to form at the exit.…”
Section: Under-expanded Hydrogen Jetsmentioning
confidence: 99%
“…The authors specifically concluded that the resolution that they employed was not adequate to resolve these details. Under-expanded jets have been studied for air and gaseous fuels (primarily natural gas), experimentally [31][32][33][34][35] and by LES [36][37][38][39]. In a recent publication on under-expanded jets, Scarcelli et al [40] validated RANS predictions of a sonic argon jet, injected at a flow rate corresponding to 100 bar nominal injection pressure into atmospheric environment, against experimental data obtained by means of X-ray radiography.…”
Section: Introductionmentioning
confidence: 99%